Physical, Chemical, and Organoleptic Properties of Ice Cream with the Addition of Loka Pere Flour - Mayangsari, Riska; Kasma, Andi Sri Rahayu; Abdullah, Anisa Dwirizky (Jurnal Ilmiah Kesehatan (JIKA), 2025)
The use of local food ingredients in ice cream production remains limited, highlighting the need for alternative ingredients that can improve its nutritional value. Loka pere flour is a promising local substitute to enhance the quality of ice cream. This study aimed to determine the effects of adding loka pere flour on the physical, chemical, and organoleptic properties of ice cream.This experimental study employed a Completely Randomized Design (CRD) with four formulas and three replications. Parameters tested included overrun, melting time, nutritional content (carbohydrates, protein, fat), and organoleptic attributes (color, aroma, taste, texture). Data were analyzed using analysis of ANOVA followed by Duncan’s post hoc test. Results showed that loka pere flour addition influenced the physical and sensory qualities of ice cream. Formula 3 had the highest overrun value at 43,44%, while Formula 2 recorded the longest melting time at 36.98 minutes per gram. Organoleptic testing revealed that Formula 2 (with 20% loka pere flour) was the most preferred by panelists, characterized by a yellowish-white color, banana-like aroma, sweet taste, and smooth texture. This formula also contained 20,52% carbohydrates, 2,21% protein, and 5,6% fat. In conclusion, adding loka pere flour particularly at a 20% concentration can improve the physical and organoleptic quality of ice cream while enhancing its nutritional profile. Loka pere flour has strong potential as a local substitute ingredient in the development of more nutritious ice cream products.